Beware of the Potential Risks for Polygoni Multiflori Caulis-Induced Liver Injury - Kong, Wei-Song; Zhou, Gui; Xu, Li-Wei; Wang, Kun; Feng, Yi-Ming; Tao, Li-Yu; Xie, Rui-Fang; Yang, Ming; Zhou, Xin (Frontiers in Pharmacology, 2022)
Background: Reynoutria multiflora (Thunb.) Moldenke (PM) is a widely-used medicinal plant in China whose root and stem are included in the Chinese Pharmacopoeia as Polygoni Multiflori Radix (RPM), Polygoni Multiflori Radix Preparata (PMP) and Polygoni Multiflori Caulis (PMC). The hepatotoxicity of RPM and PMP are concerned by public while the risk of PMC is ignored. Purpose: Here, we investigate the potential risks for PMC-induced liver injury from clinical, chemical and animal features. Study design: Firstly, we analyzed the 12-month usage of RPM, PMP and PMC in Longhua Hospital. Secondly, we determined the contents of gallic acid, cis-2,3,5,4’-tetrahydroxy-stilbene-2-O-β-D-glucoside (cis-SG), trans-2,3,5,4’-tetrahydroxy-stilbene-2-O-β-D-glucoside (trans-SG), emodin-8-O-β-D-glucoside (EG), physcion-8-O-β-D-glucoside (PG), emodin and physcion in the water extracts from 15 batches of RPM, PMP and PMC. Thirdly, we probed the hepatotoxic effect of RPM, PMP and PMC in mice and explored the mechanism of cis-SG and trans-SG causing the liver injury at the dosages based on our results from the first and second parts. Results: PMC had nearly five times amount of usage in both outpatient prescriptions and inpatient orders than RPM and PMP did. 68% dosage of PMC was 30 g. The contents of cis-SG, trans-SG and emodin in PMC water extracts were significantly lower than those in RPM and PMP water extracts. PMC induced milder idiosyncratic liver injury for its lower content of cis-SG and trans-SG than its root counterparts. Conclusion: The potential risks for PMC-induced liver injury should be fully aware of.